Nivel de ansiedad y estrés postraumático en activos y retirados de las Fuerzas Militares pertenecientes al Batallón La Popa (2022)
It can be considered that traumatic experiences can manifest terror and helplessness in individuals, placing the subject who experiences this type of situation in physical and psychological danger, leaving the victim in an emotional state unable to overcome it by himself, that is why it caused interest to execute this study which aimed to compare the level of anxiety and post-traumatic stress in active and retired members of the Military Forces of the La Popa Battalion in the city of Valledupar, 2022-I, is a quantitative, cross-sectional-descriptive research, with a sample of 51 participants, all of them male, 38 active military and 13 retired ex-military, to whom the Hamilton Anxiety Scale and the Post-traumatic Stress Disorder Symptom Severity Scale (EGS-R)